The Interaction of Polyglutamine Peptides with Lipid Membranes Is Regulated by Flanking Sequences Associated with Huntingtin - Burke, Kathleen A. (American Society for Biochemistry and Molecular Biology, 2013)
Huntington disease (HD) is caused by an expanded polyglutamine (poly(Q)) repeat near the N terminus of the huntingtin (htt) protein. Expanded poly(Q) facilitates formation of htt aggregates, eventually leading to deposition of cytoplasmic and intranuclear inclusion bodies containing htt. Flanking sequences directly adjacent to the poly(Q) domain, such as the first 17 amino acids on the N terminus (Nt17) and the polyproline (poly(P)) domain on the C-terminal side of the poly(Q) domain, heavily influence aggregation. Additionally, htt interacts with a variety of membraneous structures within the cell, and Nt17 is implicated in lipid binding. To investigate the interaction between htt exon1 and lipid membranes, a combination of in situ atomic force microscopy, Langmuir trough techniques, and vesicle permeability assays were used to directly monitor the interaction of a variety of synthetic poly(Q) peptides with different combinations of flanking sequences (KK-Q(35)-KK, KK-Q(35)-P(10)-KK, Nt17-Q(35)-KK, and Nt17-Q(35)-P(10)-KK) on model membranes and surfaces. Each peptide aggregated on mica, predominately forming extended, fibrillar aggregates. In contrast, poly(Q) peptides that lacked the Nt17 domain did not appreciably aggregate on or insert into lipid membranes. Nt17 facilitated the interaction of peptides with lipid surfaces, whereas the poly(P) region enhanced this interaction. The aggregation of Nt17-Q(35)-P(10)-KK on the lipid bilayer closely resembled that of a htt exon1 construct containing 35 repeat glutamines. Collectively, this data suggests that the Nt17 domain plays a critical role in htt binding and aggregation on lipid membranes, and this lipid/htt interaction can be further modulated by the presence of the poly(P) domain.